REKONSTRUKSI KURIKULUM SMAN 2 SUTERA: DARI EVALUASI DOKUMEN & IMPLEMENTASI KE MODEL KURIKULUM IDEAL DI ERA DIGITAL - Sefrinal, Sefrinal; Handayani, Revi; Sari, Filma Alia; Rizal, Fahmi; Ambiyar, Ambiyar (STKIP Pesisir Selatan, 2025)
This study aims to analyze and evaluate the curriculum implemented at SMAN 2 Sutera, both at the document and implementation levels, and to formulate a hypothetical model of an ideal curriculum relevant to the demands of the digital era. The research employed a mixed-methods approach with a sequential explanatory design, beginning with a qualitative analysis of curriculum documents (syllabi, lesson plans, and school programs), followed by surveys and interviews with teachers, students, and school stakeholders. The findings reveal that although the current curriculum at SMAN 2 Sutera accommodates several aspects of 21st-century competencies, there remains a gap between curriculum planning and classroom practice—particularly in the integration of digital technology, enhancement of information literacy, and the application of project-based learning. Based on these findings, this study proposes an adaptive digital-based curriculum model that emphasizes teacher-student collaboration, the use of interactive learning technologies, and the development of critical, creative, communicative, and collaborative (4C) competencies. This model is expected to serve as a reference for developing a contextual, innovative, and future-oriented senior high school curriculum in Indonesia.